Food-sharing vampire bats are more nepotistic under conditions of perceived risk - Carter, Gerald G.; Wilkinson, Gerald S.; Page, Rachel A. (Behavioral ecology, 2017)
When rescue behavior is more risky, rescuers should be more biased towards closer kin. We tested this idea using food-sharing vampire bats. We created a risky “rescue condition” where donors had to descend from the safety of dark roosting locations and feed a bat trapped in an illuminated cage on the floor. As expected, the increased risk for donors led to smaller and less frequent food donations that were also more kin-biased. Risk exaggerated nepotism.